The Role of a Muslim Artist - Noor Idayu Abd Wahid; Khalif Muammar A. Harris (Fakultas Agama Islam Universitas Wiralodra, 2022)
Tracing the history of human civilization, works of art have existed for a long time, and have been made for various purposes from good to bad. Because of that, an artist has the ability to influence others through their artwork. Certainly, there are values ​​that formed the basis for them to function as an artist. But today, the never-ending conflict of values ​​due to the influence of Western secularization has confused Muslims on the values ​​they should uphold. This article then is aimed to clarify the role of a Muslim artist based on the Islamic values. This is a library research study which applies the conceptual analysis methodology. An evaluation was done on the concepts of Islamic art according to scholars explaining the worldview of Islam and the roles of artists. This study finds that a Muslim artist is responsible to 1) bring other people to know and acknowledge Allah SWT; 2) invite to good and forbid evil; 3) produce artworks that are compliant with Islamic law and principles; and 4) to make art as a medium of good conduct instead of an end in itself.